Technical and Architectural Study on the Application of Photovoltaic Panels in Building Envelopes: Case Studies of the Shanghai Electric Power Building and the Adidas Flagship Store, Beijing - Priscila, Anastasia Julia; Sahid, Sahid; Nugroho, Nancy Yusnita (Jurnal Arsitektur ZONASI, 2025)
The decline of fossil fuel resources and the increasing global demand for electricity have intensified the need for renewable energy. Solar energy, one of the most abundant and sustainable energy sources, can be actively harnessed through photovoltaic systems. The use of photovoltaic systems can be integrated into building envelopes, one of which is on the facade. The integration of photovoltaics on façades must consider both technical factors such as location, climate, and panel type, and architectural aspects related to aesthetics. China, as one of the world’s leading photovoltaic industries, provides valuable case studies of buildings that integrate photovoltaic systems into their envelopes. This study aims to examine the application of photovoltaic panels from both technical and architectural perspectives in two buildings: the Shanghai Electric Power Building and the Adidas Flagship Store Beijing. A case study research method was employed, consisting of a literature review, analysis (including solar orientation, photovoltaic panel materials, and façade area) of the two case study buildings, and conclusion drawing. The results indicate that both buildings successfully demonstrate the application of photovoltaic systems within their respective contexts. The Shanghai Electric Power Building illustrates the significant potential of PV systems in retrofitting existing architecture, whereas the Adidas Flagship Store highlights the synergy between aesthetics and technological functionality in new architectural design. The integration of renewable technology and architectural design is essential in creating buildings that are not only environmentally sustainable but also possess high aesthetic and economic value for the future.